Penguatan Literasi Bahasa Arab Dasar melalui Pengembangan Modul Ajar Berbasis Desain Visual (Postcard dan Poster) bagi Santri TPQ Al-Firdaus Jaten, Makamhaji - Masykur Amanu; Dhea Cahyani; Defi Anita listari; Ummi Hasanah; Triono Ali Mustofa (Universitas Pahlawan Tuanku Tambusai, 2026)
Basic Arabic literacy is essential to introduce from an early age to support children’s understanding of Islamic teachings and language development. However, learning activities at Al-Qur’an Education Parks (TPQ) generally focus more on Qur’anic reading skills. This community service program aimed to enhance basic Arabic literacy among students at TPQ Al Firdaus Jaten Makamhaji through the development of visual design-based teaching modules in the form of postcards and posters. The program employed a Participatory Action Research (PAR) approach, encompassing planning, implementation, observation, and evaluation stages involving students, ustadz/ustadzah, and the service team. Activities included introducing mufrodat (vocabulary), practicing simple conversations, utilizing visual media, conducting educational games, and mentoring teachers. The results indicated improvements in students’ ability to recognize and retain Arabic vocabulary, as well as increased motivation and participation in learning activities.